INTERSECTION BETWEEN LEADERSHIP STYLES AND INTENTION TO STAY: A PERSPECTIVE FROM MANUFACTURING SMES IN MALAYSIA - Dr Ahmad Fadhly Arham; Dr Rizuwan Abu Karim; Siti Nur Athirah Binti Mohd Fauzi (International Journal of Accounting, Finance and Business, 2021)
This concept paper is to investigate the relationship between transformational leadership styles and transactional leadership styles towards employee intention to stay in manufacturing SMEs Malaysia. Contribution of Small Medium Enterprises (SMEs) all around the globe including Malaysia cannot be repudiated as this industry has contributed in GDP as well as in job employment. However, every organization including SMEs has facing a critical issue in which their employees keep on leaving the organization and this has turned out to contribute to high turnover rate. In this paper, it is contended that the employee turnover rate within the organization is subjected to different leadership styles being practiced by the leaders of the SMEs. This research provides numerous implications. The implications for SMEs industry are as follows. First, is to identify the best practice of leadership styles as perceived by the employees for their organization. Second, is to identify which leadership styles between transformational leadership and transactional leadership that is effective to influence employee to remain working in the organizations.